Assessing the risk of plant species invasion under different climate change scenarios in California. (30th September 2021) - Renteria, Jorge L.; Darin, Gina M. Skurka; Grosholz, Edwin D.
Abstract: Using species distribution models (SDMs), we predicted the distribution of 170 plant species under different climatic scenarios (current and future climatic conditions) and used this information to create invasion risk maps to identify potential invasion hot spots in California. The risk of invasion by individual species was also assessed using species' predicted area in combination with some biological traits associated with invasiveness (growth form, reproduction mechanisms, and age of maturity). A higher number of species would find suitable climatic conditions along the coast; the Central Western (CW) and South Western (SW) were ecoregions where a higher number of species were predicted. Overall, hot spots of species distribution were similar under current and future climatic conditions; however, individual species' predicted area (increase or decrease) was variable depending on the climate change scenario and the greenhouse gas emission. Out of the 170 species assessed, 22% ranked as high-risk species, with herbs, grasses, and vines accounting for 78% within this risk class, and a high proportion (67%) of Asteraceae species ranked as high risk. This study suggests that current climatic conditions of the central and south coastal regions of California would be considered as hot spots of new invasions, and for some species this risk might increase with hotter and drier future climatic conditions.